The Role of Foreign Direct Investment In The Relationship Between Global Innovation Index and Gross Domestic Product - Cemberci, Murat; Civelek, Mustafa Emre; Comert, Perlin Naz (GURUKUL KANGRI UNIV, FAC MANAGEMENT STUDIES, 2022)
Purpose: In today's world; where technology, capital and workforce are in a rapid flow across borders; quantitative indicators, that provide insight into the economic and innovative performance of countries, are of key importance for decision makers. One of these indicators is Foreign Direct Investment (FDI); which is not only a mechanism that drives competition and economic development, but is also an international capital flow. This paper investigates whether FDI has a mediator role in the relationship between Global Innovation Index (GII) and Gross Domestic Product (GDP). Design/Methodology/Approach: The mediator variable analysis was conducted based on the secondary data of FDI, GII and GDP of 43 countries which has been obtained from the World Bank between 2014 and 2018. Findings: As a result of the analysis, all hypotheses were accepted. Consequently, a positive and significant relationship was found between the Global Innovation Index (GII) and Gross Domestic Product (GDP), and it was found statistically significant that Foreign Direct Investment (FDI) has a mediator role in this relationship. Originality: In the literature, there is not any research that explains the role of FDI in the relation between Global Innovation Index (GII) and Gross Domestic Product (GDP). In order to address the gap, this study investigates whether FDI has a mediator role in the relationship between GII and GDP.
Keywords: Foreign Direct Investment; Global Innovation Index; Gross Domestic Product; ECONOMIC-GROWTH; EMPIRICAL-ANALYSIS; IMPACT; DETERMINANTS; COUNTRIES; TRADE; FDI; ICT; Business & Economics